Valuing elite sport success using the contingent valuation method: A transnational study - Funahashi, H.; Shibli, S.; Sotiriadou, P.; Mäkinen, J.; Dijk, B.; De Bosscher, V. (Sport Management Review, 2020)
The contingent valuation method was used to value elite sport success on a transnational basis. Samples of adults in five countries were asked for their willingness to pay for a `high-performance sport fund` in order to avoid a decline in medal performance at the next Summer Olympic Games. Respondents in the more successful medal winning countries reported higher willingness to pay than those in the relatively less successful countries. In line with welfare economics theory, more medals won appears to be linked with more utility among individuals.